Tren dan Peluang Cross-Platform Mobile App untuk Developer Pemula - Mirza Ilhami (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2021)
The development of cross-platform based mobile applications has grown rapidly in the last five years. From a developer's point of view, the many technologies that must be studied make them confused about which programming language to master because it will correlate with the time required and technology adoption by the industrial world. From an industry point of view, the challenge faced is determining the right framework or programming language and tools for their application. It also correlates with development time and costs, as well as finding the best talent with the technology. The purpose of this paper is to provide insight, trends and perspectives to new programmers who want to start a career and industry related to technology used in cross-platform mobile applications by looking at the results of surveys conducted by Stackoverflow, SateOfJS and Ionic Framework for the past 5 years. So this will help new programmers and industry in choosing the right technology and framework. The author found that currently JavaScript has mastered the frontend, backend and test tools. Regarding cross-platform frameworks, we find the Ionic Framework, React Native to be the most widely used.